GREEN FINANCE IN UZBEKISTAN: CURRENT STATE AND DEVELOPMENT PROSPECTS (European Journal of Economics, Finance and Business Development, 2024)
The purpose of the work is to assess the current state of "green" financing in the Republic of Uzbekistan and develop proposals to stimulate its further development. The methodological basis of the study was the use of modern economic and mathematical methods: cluster analysis, regression model construction. This allowed us to obtain results that have both a certain scientific novelty and practical significance. The evolution of scientists' views on the concept of sustainable development and the formation of a "green" economy is considered. The current state of "green" financing in the Republic of Uzbekistan for 2000-2018 is analyzed. Clustering of the subjects of the Republic of Uzbekistan was carried out according to the level of environmental investments and current costs for environmental protection, which made it possible to identify regions that are leaders and outsiders of these processes, as well as to establish the fact of a high level of regional differentiation in financing "green" projects. The regression model constructed by the authors allowed us to prove that with an increase in investments in fixed assets aimed at environmental protection and rational use of natural resources by 1 million soums, the GDP of the Republic of Uzbekistan will increase by 0.1 billion soums. With an increase in the current costs of organizations for environmental protection by 1 million soums. The level of GDP of the Republic of Uzbekistan will increase by 0.3 billion soums. The article concludes that in order to stimulate the development of "green" financing in the Republic of Uzbekistan, it is necessary to implement a set of measures providing for the formation of an appropriate regulatory framework; the development and use of new tools for financing "green" projects; the creation of a specialized banking institution.